Strategi Experiental Marketing Akal Production Pada Event Loal Museum Melalui Media Sosial TikTok - ., Maghfirah; Eriend, Dion (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This Final Project Report is an application of project-based curriculum or other forms compiled based on the author's experience while making projects at Akal Production company as an event organizer located in Padang City. While in the company, the author created a unique event project that has never existed in Padang City, namely an interactive museum that emphasizes visual creativity. Loal Museum is a project idea created so that the citizens of Padang have a new place of art, entertainment and recreation. The event was held for 1 full month located in Fabriec Block, Parupuk Tabing. This event carries the theme Galaxy Pop Art by using the #MagicExperienceOfLoal campaign. Loal Museum has several rides whose purpose is to provide direct experience to visitors. In addition, the author who is part of Akal Production as Chief Of Admin and Social Media to manage the promotion of this event so that it has many enthusiasts and visitors who come every day of the month. This Experiental Marketing strategy is carried out through TikTok and Instagram social media. This strategy is used to create an interesting experience to make this event viral and known by many people is through TikTok social media. Through the experiental marketing strategy, many visitors come through their curiosity and experience firsthand the experiences that many other visitors have felt. The obstacle that the author faced when running thisLoal Musem project was the many communication errors that occurred.